Peningkatan Kapasitas (Capacity Building) Pengasuh Pondok Pesantren Dalam Menyiapkan Santri Masagi - Koswara, Nandang; Zam’an, Paojan; Sopandi, Uus; Jabar, Reny; Maemunah, Rinrin Siti (Journal of Education Research, 2024)
The purpose of this community service activity is to increase the capacity of Islamic boarding school caregivers in preparing masagi students through in-house training and focus group discussions. Capacity Building for caregivers of Syamsul Ulum Muhammadiyah Islamic boarding school in preparing masagi students, among others: by joining extra-curricular and making cooperation with Bapelkes Krakatau Steel and R-Mifa cageur; By making habits of worship, doing good attitude and doing routine activities at Islamic boarding school or school bageur, bener, by learning religious based science at Islamic boarding school and general based science at MTs and SMA or pinter, and by practice of field's dedication, training of multimedia and public speaking and joining seminar on entrepreneurship or singer. Yet, facilitating of singer aspects especially life skills training or programs on entrepreneurship has not been optimal yet. The obstacles there are no program of life skills training or entrepreneurship, no human resources which focuses in applying both programs, entrepreneurship learning is still co-curricular at senior high school and limitations of budget and facilities. The solutions which can be done are Islamic boarding school make specific program about life skills training or entrepreneurship agree with students' interest and talent, prepare a caregiver of Islamic boarding school who focuses in applying those programs and prepare special budget for training programs and providing facilities .